The Influence of Sustainable Marketing and Brand Image on Purchase Decision on Brands Sejauh Mata Memandang - Mulyaningsih, Nani; Tobing, Rudy P. (Business and Investment Review, 2023)
The increasing development of the fashion industry in Indonesia has a major impact on improving the economy as well as environmental and social issues because it threatens global sustainability. This has encouraged fashion industry players to shift their marketing concept to a more sustainable one to create a positive brand image as well as encourage purchase decisions. This study aims to determine the effect of sustainable marketing and brand image on purchase decisions for the brand Sejauh Mata Memandang. This research was conducted using a quantitative approach and explanatory research design with a sample of 142 respondents. The instrument used is a questionnaire or questionnaire. The test instrument used is the validity test and reliability test. Data analysis used is descriptive analysis, with hypothesis testing using multiple linear regression tests, t tests, f tests, and the coefficient of determination. The results of the study show that (1) sustainable marketing has no significant effect on purchase decision (2) brand image has no significant effect on purchase decision (3) sustainable marketing and brand image have no significant effect on purchase decision. There are several factors that cause the hypothesis in this study to be rejected including the lack of awareness of respondents on sustainable issues, the gap between intentions and actions, product quality, personal style, and the influence of well-known figures. This research is limited because it is only done on fashion brands Sejauh Mata Memandang.